"Music Therapy Was Never on the Table": Perspectives of Parents of Young Autistic Children. (25th July 2022) - Hernandez-Ruiz, Eugenia; Lehrer, Gabriel
Abstract: Parent coaching of music interventions is emerging as a viable model for families with young autistic children, yet recruitment difficulties have been apparent in previous studies. Understanding parent perspectives of early intervention services is critical to ensure that interventions are acceptable, feasible, and effective for all family members. In order to understand possible parental resistance to this type of parent education, we explored perspectives regarding music therapy, research, and parent coaching in parents of young autistic children. Fourteen parents attended virtual focus groups to discuss their experiences. We used a descriptive phenomenological approach to uncover the essence of their experience. Our findings indicate that, contrary to our preconceptions, participants did not show negative dispositions towards music therapy, research, or parent coaching. Instead, most participants had very little or no knowledge of music therapy services. They had limited experience with research in general, and only two participants had experienced music therapy directly. Several participants had varying amounts of experience with parent participation or parent coaching outside of music therapy and shared positive experiences with it. Parents seemed willing and eager to learn music strategies to support their children and saw value in the use of music for their child's development. First-contact providers (i.e., early interventionists and diagnosticians) and social media seem influential in parents' decision-making as they navigate early intervention services soon after diagnosis. Music therapy organizations are encouraged to design targeted efforts to make information on music therapy available through these sources.